Localising Pop Yeh Yeh With Malay Musical Elements And Language In The 1960s - Jocelyn, Marcia Ng Siu Lyn (2024)
The term ‘Pop Yeh Yeh’ refers to the genre of Malay popular music that emerged in the 1960s in Malaysia and Singapore influenced by western acts like The Beatles, The Shadows, and The Rolling Stones from the United Kingdom. The music of Pop Yeh Yeh was accompanied by a kugiran (upbeat guitar band) consisting of three guitars and a drum set, mirroring the configuration used by the Western bands of the era. Pop Yeh Yeh music faced disapproval from seasoned musicians who viewed the musicians as amateurs who had no music education and produced songs of poor quality. Through in-depth interviews with people in the music industry and analysing the music of local musicians recorded on vinyl records, this thesis shows that Pop Yeh Yeh music was inspired by and shared many similar characteristics with the popular bands and music of the United Kingdom in the 1960s. Although Pop Yeh Yeh was initially imitative of Western pop styles, local musicians such as L. Ramli and A. Rahman Hassan with their bands Orkes Teruna Ria and Orkes Nirwana eventually localized their music by integrating Malay asli vocal styles, the Malay language, and lyrics about Malaysian life with Western surf rock rhythms, vocal harmonies, and musical form. They also created album covers that illustrated people in Malaysian-style clothing, and scenes from Malaysia. This study shows that although Pop Yeh Yeh music followed western musical styles, local musicians included Malay characteristics and musical elements that made it unique to Malaysia.